Reservoir characterization of the Dokan and Gulneri Formations (Upper Cretaceous) from selected wells in Khabbaz Oil Field, Kirkuk area, Northern Iraq - Qader, Fouad M. (Sulaimani Journal for Pure and Applied Sciences, 2018)
The evaluations of reservoir characterization for Cretaceous Dokan and Gulneri Formations have been selected for this study in Khabbaz Oil Field- Northern Iraq. The Cenomanian Dokan Formation is an open marine oligosteginal limestone ranged in thickness between 21 and 29 meters in this field, and it is overlain by 11 to 14m thick of Gulneri Shale Formation, both are underlying by the thick rock unit of Qamchuqa Formation (Mauddud and Shu'aiba). The full set log data for the seven wells of (Kz-1, Kz-3, Kz-4, Kz-5, Kz-11, Kz-14, and Kz- 16) were available, also some general data derived from the wells (Kz-2, Kz-6, Kz-7, Kz-8, Kz-9, Kz-10, Kz-12, Kz-13, Kz-15, and Kz-21). The log data have been used in evaluating the reservoir properties of the two rock units. The detected lithologies from Neutron-Density combination log showed that Dokan Formation is mostly limestone dominated, and the Gulneri Formation is shale rock. From the log data different type of reservoir properties (clay content, porosity, fracture index, and gas crossover) have been estimated. Additional core sample measurements (capillary pressure, porosity, permeability, and thin sections) were used for supplementary analysis.
Keywords: Khabbaz Oil Field; Reservoir Characterization; Dokan Gulneri Formations